UU No. 5 of 2014 as The Basis for BKN's Collaborative Work with The Ministry of PAN and Bureaucracy in the ASN Context - Marjan - Miharja (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
One area of change in bureaucratic reform can be implemented if there is a competent state civil apparatus. One of the competent civil servants is in the field of human resources, namely employees who have an educational background according to the position given to them. Bureaucratic reform in Indonesia conducted through Law No. 5 of 2014 on State Civil Apparatus has not yet presented its maximum results. The rising cases of buying and selling job promotions by the head of the region is one of the indicators. The purpose of this research is to describe and analyze the relationship between the National Civil Service Agency and the Ministry of State Apparatus Utilization and Bureaucratic Reform based on Law No. 5 of 2014 on State Civil Apparatus. The research used the descriptive qualitative method with normative juridical analysis and data collection is carried out through literature studies. The secondary data collected from documents and texts related to the research topic, be it books, articles journals, or others. The results of this studyshow that as long as the civil service development officials are still carried out by political. This results of this study show that as long as the oversight task is still carried by political officials, and bureaucracy dependence on politics is simultaneously strong, political neutrality and professional bureaucrats are difficult to be created. While, the negative impact will be received by people as the users of their services. This research recommends that the role of oversight officers is given to bureaucratic career officials through the revision of UU ASN. KASN will consequently have a role to ensure that every bureaucrat will perform its role as the executor of any policy made by political officials. With this revision, thus, ASN will be a professional in carrying out its duties, which needed in making effective governance